INTEGRASI STRATEGI KOMPETITIF DAN KOOPERATIF DALAM EKOSISTEM BISNIS GLOBAL: SEBUAH PERSPEKTIF BARU - Sabardiman, Ken; Mustofa, Amirul; Yunus, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The traditional distinction between competitive and cooperative strategies is becoming less relevant in today’s complex and dynamic global business environment. This article offers a new perspective by integrating both approaches through the concept of coopetition—a combination of collaboration and competition—as an adaptive and sustainable strategy. Drawing on a literature review and conceptual analysis, the study examines how firms can simultaneously cooperate and compete within the global business ecosystem, considering contextual factors such as the growth of emerging economies, political dominance, technological disruption, and social demands. The findings indicate that a well-balanced application of coopetition can enhance innovation, share risks, optimize resources, and strengthen long-term competitive advantage. This study contributes to the theoretical development of strategic management and provides practical guidance for business practitioners in designing strategies that are responsive to global environmental changes.